THE INFLUENCE OF THE USE OF QRIS APPLICATION TECHNOLOGY AND FINANCIAL LITERACY ON BUYING AND BUYING TRANSACTION ACTIVITIES IN MSMEs IN LHOKSEUMAWE CITY - Hikalmi, Hikalmi; Chyntia, Eka; Maryana, Maryana; PG, Eko Gani; Tazrin, Cut Nisrina (J-ISCAN: Journal of Islamic Accounting Research, 2023)
The role of MSMEs in Indonesia is often linked to government efforts to reduce unemployment, fight poverty and equalize income. Collaboration between MSMEs and electronic money organizers will be able to advance the Indonesian economy. Quick Response Code Indonesian Standard or usually abbreviated as QRIS (pronounced KRIS) is a combination of various types of QR from various Payment System Service Providers (PJSP) using a QR Code. Currently QRIS is used in all payment applications which can be used in all shops, traders, stalls, parking lots, tourist tickets, donations (merchants) with the QRIS logo. Someone with good financial literacy can see money from a different perspective so they can control their financial condition. In its implementation, QRIS still has various obstacles, one of which is the level of financial literacy of the Lhokseumawe City MSME community which is still low so that people's understanding of digital finance is still lacking and not evenly distributed. This research aims to examine whether the QRIS application implemented by MSMEs influences the increase in buying and selling transactions in the community, as well as whether people's financial literacy influences transaction decisions using the QRIS application. The results of this research show that financial literacy and ease of use have a positive and significant influence on the choice of using QRIS by MSMEs in the city of Lhokseumawe. Financial literacy has a positive and significant impact on MSME transactional operations in the city of Lhokseumawe. This shows how people, especially MSMEs, have strong knowledge and skills in terms of financial management, which influences their choice to use one of the financial technology products, namely QRIS.